Investment in education as a factor of economic growth: evidence for Portugal and comparative analysis with the EU - Ribeiro, Sandra (2023)
The role of education, in social and professional terms, is of undeniable relevance to individuals, so its investment in the most varied forms, is very important to enhance their abilities and "capitalize" knowledge, which can be used in the future to increase productivity in individual terms and therefore at the level of each country. we looked at a more theoretical aspect, which would allow us to explain the different approaches of certain authors with a strong participation in this topic, namely those of Solow (1956) and Lucas (1988), which are essential for carrying out this research. In addition to the definition of objectives and after their relevance is justified, this study contemplates the focus given to the methodological component, which is based on the search for results that may corroborate or refute the theories defended, through an exhaustive analyze and a Statistic model, which could combine the endogenous and exogenous variables targets of Investigation.